Drones and Privacy - Takahashi, Timothy T (Science and Technology Law Review, 2013)
The Los Angeles Times recently reported the first instance in which military “drone” aircraft participated in the arrest of United States citizens on United States soil. A Customs and Border Protection Predator B drone played a key role in the arrest of Rodney Brossart and his three sons at their North Dakota ranch. With the conclusion of the Second Gulf War, pressures mount to utilize surplus drones and other quasi-military drone technology on the home front. This monograph summarizes the known facts of the Brossart case, describes the capabilities of military surveillance “drone” aircraft, and discusses whether a case similar to Brossart could serve as a catalyst for Supreme Court action. If such a case were appealed, the Supreme Court could issue a judgment articulating a new standard controlling how the Fourth Amendment governs robotic surveillance.